Majas Dan Makna pada Lirik lagu “Seperti Tulang” Karya Nadin Amizah - Shadrina Kaysa Mazaya; Dea Putri Ananda (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of making this journal is to analyze the figure of speech and the meaning contained in the lyrics of Nadin Amizah's song entitled